Tahapan Belajar Al Qur’an Menggunakan Huruf Hijaiyah Isyarat bagi Anak dengan Hambatan Pendengaran - Bayu Pamungkas; Hermanto Hermanto (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
The purpose of this research article is to describe learning the Qur'an with sign language which is carried out at the Darul A'shom Special Islamic Boarding School for the Deaf, Yogyakarta. Qualitative research methods used in this study with observation, interviews and documentation as data collection techniques. The results of the study explain that children with hearing impairments are able to read and memorize the Qur'an using sign language through sign hijayah letters which are applied in the cottage through five stages of learning and three times of learning implementation.